PROTOTYPE DESIGN OF 4 PROBE METHOD BASED ON MICROCONTROLLER WITH MEMORY CARD STORAGE MODULE - Imam Sya'roni; Nugrahani Primari Putri; Lydia Rohmawati (Jambura Physics Journal, 2022)
The goal of this study is to create a prototype that uses a microcontroller to determine the physical phenomenon worth of a fabric victimisation, method by four-point probe. The amendment in resistance of a material once an electrical current flow through it's wont to quantify electrical conductivity. The example took measurements and saved them as data.txt. Using IC 741 100X gain amplifier circuit, prototype amplifies the output voltage and current for convenient monitoring. The source flag value is used in prototype calibration; the tolerance value for the measurement uncertainty of voltage is 2.1 percent and tolerance value of uncertantanty of current is 2.1 percent, respectively, based on comparisons with the calibration output. For voltage readings, prototype's measurement accuracy is 97.89 percent, and for current assignments, it's 97.64 percent. The output values will be saved and analyzed before being graphed to determine the material's conductivity value. Pani, a substance with a composition of 0.25 M anilin + 0.5 M HCL, was used to test the electrical conductivity of prototype Four Point Probe. The experiments were carried out by varying the voltage from 1 to 5 until the value of material conductivity Pani was between 0.9 and 1,25 x 107 (m)-1. Range 73.47 percent linearity value.